Forum Edukasi Orang Tua tentang Tumbuh Kembang Anak di HEbAT Community Tegal Raya - Umriaty Umriaty; Nora Rahmanindar; Vivin Avianti Oktavia; Siti Habibah; Reyska Aleyda; Siti Khumayah; Novita Nur Agustin (Universitas Muhammadiyah Semarang, 2024)
Basically, every child will go through a growth and development process according to their age stages. To properly monitor children's growth and development, parents, health workers, educators, cadres and other staff who are interested in children's growth and development need to take their respective roles. Because the process of children's growth and development is almost the same, knowing the characteristics and principles of children's growth and development will make it easier for parents to provide growth and development stimulation in accordance with what is needed and expected by children to achieve optimal growth and development. One of the efforts to overcome this is by educating parents about stimulating growth and development using simple instruments. One of the tools/instruments used to determine whether a child's development is normal or whether there are deviations is by using the KIA book. This service activity aims to increase parents' knowledge and skills in monitoring children's growth, development and stimulation by utilizing the parenting activity community that already exists in Tegal City, namely the HEbAT Community. This activity takes the form of providing material on parenting concepts and improving skills in monitoring and stimulating children's development. The learning stages contain parenting concepts according to Nurturing Care recommended by WHO. At the practical stage, there will be practice assessing children's development through the KIA book. The monitoring results will show the child's developmental status and the type of stimulation needed. The service was carried out on May 30 2024 at the Pendopo, East Tegal District, Tegal City, which was attended by 32 mothers of toddlers and their children.